Metabolomic fingerprints of clustered preterm and term neonates – a pilot study - Miłosz Lorek; Miłosz Lorek; Teresa Joanna Stradomska; Anna Siejka; Janusz Fuchs; Dominika Januś; Aneta Gawlik-Starzyk (Frontiers in Endocrinology)
IntroductionAdrenal steroidogenesis plays a pivotal role in neonatal adaptation, and advanced steroid profiling offers novel insights into disease risks and personalized management strategies. This study aimed to identify adrenal steroid metabolomic clusters in neonates and to correlate them with clinical outcomes.MethodsIn a prospective observational design (June 2021–July 2022), 50 neonates (12 early preterm, 18 late preterm, and 20 full-term) admitted with respiratory distress underwent continuous 24-hour urine collection via an urinary catheter. Steroid profiles were analyzed by gas chromatography–mass spectrometry. K-means clustering was employed to classify the metabolomic data, which were subsequently correlated with mortality, bronchopulmonary dysplasia (BPD), small for gestational age (SGA), and intraventricular hemorrhage (IVH).ResultsK-means analysis delineated three distinct metabolic clusters. Cluster 1 displayed a profoundly suppressed steroidogenesis (low C19 and C21 excretion, diminished 3β-hydroxysteroid dehydrogenase and 5α-reductase activities), correlating with an increased incidence of BPD, high mortality risk scores, and significant rates of SGA/intrauterine growth restriction. Cluster 2 exhibited adrenal hyperactivation with elevated cortisol/cortisone derivatives, moderately increased C19/C21 metabolites, and partial 3β-HSD deficits, associated with a heightened risk of IVH and mortality. Cluster 3 showed robust steroidogenesis (high C19/C21 excretion and high 3β-HSD/5α-reductase activities), accompanied by the lowest mortality rates and absence of BPD or SGA/IUGR.ConclusionsSuppressed steroidogenesis increased BPD, SGA, and mortality, while excessive cortisol output in Cluster 2 was associated with a higher risk of IVH. Robust steroidogenesis supported favorable outcomes, highlighting the potential for metabolome-guided interventions.